2017
DOI: 10.1080/08941939.2017.1334844
|View full text |Cite
|
Sign up to set email alerts
|

Intermittent Ischemic Preconditioning Protects Against Hepatic Ischemia-Reperfusion Injury and Extensive Hepatectomy in Steatotic Rat Liver

Abstract: Hepatic steatosis and IRI after major liver surgery largely affect morbidity and mortality. Intermittent IPC, 24 hours before IRI and extensive hepatectomy, presents higher 30-day survival and improved liver function parameters.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
13
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 71 publications
0
13
0
Order By: Relevance
“…It has been reported that programmed transient ischemia-reperfusion during shock, or during resuscitation also has protective effects [16]. Second, the protective effect of IPC is more prominent in primary hepatic I/RI in special cases, such as fatty and senile liver [10,13,29]. This study showed that RIPC-activated autophagy plays a role in hepatoprotection after hemorrhagic shock, but to what extent autophagy is the underlying mechanism and whether RIPC plays a more prominent role in special groups need further investigation.…”
Section: Discussionmentioning
confidence: 99%
“…It has been reported that programmed transient ischemia-reperfusion during shock, or during resuscitation also has protective effects [16]. Second, the protective effect of IPC is more prominent in primary hepatic I/RI in special cases, such as fatty and senile liver [10,13,29]. This study showed that RIPC-activated autophagy plays a role in hepatoprotection after hemorrhagic shock, but to what extent autophagy is the underlying mechanism and whether RIPC plays a more prominent role in special groups need further investigation.…”
Section: Discussionmentioning
confidence: 99%
“…They have been used as animal models, mice and rats in genetic, nutritional and mixed models for the development of NAFLD ( 2 , 29 32 ). NAFLD developmental dietary models are rather more reliable research tools.…”
Section: Discussionmentioning
confidence: 99%
“…The most frequently used experimental models of NAFLD concern the choline or choline/ methionine- free diet ( 2 , 30 , 46 ). The absence of choline disrupts the synthesis of phosphatidylcholine in the liver, leading to accumulation of triglycerides in the hepatocyte and development of hepatic steatosis ( 2 , 14 , 29 , 2 ). Feeding with a choline-free diet causes severe chronic-dependent hepatic steatosis, characterized by inflammation, with or without mild fibrosis, while prolonged feeding can cause even neoplasia ( 2 , 14 , 28 30 , 46 ).…”
Section: Discussionmentioning
confidence: 99%
“…A number of animal and clinical studies have assessed the protective efficacy of IPC in liver transplantation and hepatectomy 16,17 . Some animal studies showed hepatic protection of RIPer from warm IRI 14,18 .…”
Section: Introductionmentioning
confidence: 99%